Pengaruh Sistem Akuntansi Manajemen, Sistem Pengendalian Manajemen, dan Desentralisasi terhadap Kinerja Manajerial (Studi Empiris pada Bank Perkreditan Rakyat se-Eks Karesidenan Surakarta) - Putri, Maya Sundari Cahyono, Drs. Muhammad Abdul Aris, M.Si (2017)
The purpose of this study was to test the effect of management accounting systems, management control systems and decentralization on managerial performance. Research was conducted on Bank Perkreditan Rakyat se-Eks Karesidenan Surakarta.The determination of this sample using purposive sampling method. Data obtained in this research by distributing questionnaires to the respondents. The number of respondents as many as 50 people.Analysis of data using multiple linear regression analysis. The analysis showed broad scope, integration, management control systems and decentralized significant effect on managerial performance. As for the timeliness and aggregation variable has no effect on managerial performance